THE INFLUENCE OF THE ADAPTIVE IMMUNE SYSTEM ON BEHAVIOUR, BEHAVIOURAL SYSTEMS, AND FUNCTIONAL NEUROANATOMY - Rilett, Kelly C. (My University, 2013)
Immune-brain communication has important influences on stress circuitry and stress-related behaviours. Adaptive immune deficiency through loss of lymphocytes or an absence of gut bacteria has been linked to anxiety behaviours and stress responsiveness. In these models, there is a common deficit of T lymphocytes leading to the central hypothesis that T lymphocytes influence stress responsiveness and stress-related behaviours. This project considers the effects of T lymphocyte deficiency on anxiety and fear related behaviours as well as stress responsiveness in the hypothalamic pituitary adrenal (HPA) axis. Mice lacking T lymphocytes through knockout of the T cell receptor (TCR) β and δ chains, and B lymphocytes through knockout of the immunoglobulin M μ chain, were obtained and compared to C57BL/6 control mice. Activity, exploration, anxiety, fear and spatial learning tests were employed. Separately, gene expression was assessed for genes related to stress circuitry following chronic restraint stress. Additionally, lipopolysaccharide was used to determine the stress response to an innate immune challenge that was previously shown to elicit an exaggerated stress response in mice lacking Class I Major Histocompatibility Complex (MHC) and CD8+ T lymphocytes. It was found that mice lacking T lymphocytes, but not B lymphocytes, have reduced anxiety-like behaviour but an increased fear response. TCRβ-/-δ-/- mice also had altered expression of components of the HPA axis, serotonergic receptors and NMDA receptor subunits indicating an altered response to chronic stress. Finally, TCRβ-/-δ-/- mice do not display an exaggerated stress response to an innate immune challenge suggesting a central role for Class I MHC in the stress response that is not due to the CD8+ T lymphocyte deficiency that accompanies the functional loss of Class I MHC. These studies reflect an important role for T lymphocytes specifically in the development of the stress system and stress-related behaviours and enables a deeper understanding of neuroimmune influences on stress.
Keywords: Neuroscience; Neuroimmunology; Anxiety; Fear; Stress; Neuronal Gene Expression; Immune Challenge; Behavioral Neurobiology; Molecular and Cellular Neuroscience; Behavioral Neurobiology